Decoding the secret of extracellular vesicles in the immune tumor microenvironment of the glioblastoma: on the border of kingdoms - Ghazi, Bouchra; Harmak, Zakia; Rghioui, Mounir; Kone, Abdou-Samad; El Ghanmi, Adil; Badou, Abdallah (Frontiers in Immunology, 2024)
Over the last decades, extracellular vesicles (EVs) have become increasingly popular for their roles in various pathologies, including cancer, neurological, and immunological disorders. EVs have been considered for a long time as a means for normal cells to get rid of molecules it no longer needs. It is now well established that EVs play their biological roles also following uptake or by the interaction of EV surface proteins with cellular receptors and membranes.In this review, we summarize the current status of EVs production and secretion in glioblastoma, the most aggressive type of glioma associated with high mortality. The main purpose is to shed light on the EVs as a universal mediator of inter-kingdom and intra-kingdom communication in the context of tumor microenvironment heterogeneity. We focus on the immunomodulatory EVs functions in glioblastoma-immune crosstalk to enhance immune escape and reprogram tumor infiltrating immune cells. We critically examine the evidence that GBM-, immune cells-, and microbiome-derived EVs impact local tumor microenvironment and host immune responses, and can enter the circulatory system to disseminate and drive premetastatic niches formation in distant organs. Taking into account the current state of the art in intratumoral microbiome studies, we discuss the emerging role of bacterial EV in glioblastoma and its response to current and future therapies including immunotherapies.